Feasibility and safety of outpatient radiofrequency catheter ablation procedures for atrial fibrillation. Issue 1017 (15th July 2010) - Haegeli, Laurent M; Duru, Firat; Lockwood, Evan E; Lüscher, Thomas F; Sterns, Laurence D; Novak, Paul G; Leather, Richard A
Abstract : Introduction: Percutaneous catheter ablation for atrial fibrillation (AF) is a procedure performed typically in an inpatient setting. The feasibility and safety of catheter ablation in patients with paroxysmal and persistent AF were evaluated on an outpatient basis. Methods: 230 AF ablation procedures were performed in 206 patients (74% male; mean age 56±9 years). Patients were admitted to the hospital outpatient facility in the morning for the AF ablation procedure on the same day. The ablation strategy consisted of wide area circumferential lines around both ipsilateral pulmonary veins. After monitoring in the outpatient service, patients were discharged on the same day, if they were clinically stable. Results: Mean procedure time was 201±31 min. Major complications occurred in seven patients (3%). One patient (0.4%) suffered a minor stroke and six patients had pericardial tamponade requiring percutaneous drainage. Patients could be discharged on the same day following 205 (89%) procedures. Among the 148 patients whose clinical outcome was assessed at 6 months, 127 (86%) had a reduction of the total symptomatic AF episodes, compared to pre-ablation, with a complete lack of symptoms in 101 patients (68%). Conclusion: Catheter ablation of AF on the day of admission is feasible and safe with a low risk of complications. The vast majority of the patients can be discharged on the same day.